Computer control & audit - Mair, William C.; Davis, Keagle W; Wood, D. R; Touche Ross & Co; Institute of Internal Auditors (New York : Institute of Internal Auditors, 1976)
This manual outlined a methodology for evaluating the process of internal control
includes glossaries
include index
ijb, 16/01/2019
Loans
Keywords: Auditing--Data processing; Electronic data processing departments--Management; Computer programs